THE EVALUATION OF CRUDE OIL PRICE- ARTICLE FOR IRAQ - Haidar Ali AlDulaimi; Asam mohamed Aljebory; Mustafa Jawad Kadhim A-Bakri (Scholar Express Journals, 2022)
The goal of the study is to develop a theoretical framework for evaluating crude oil prices by looking at a variety of factors that influence oil prices. Forecasting global crude oil prices, according to the research hypothesis, is dependent on a number of indicators, the most important of which are (global oil supply, global oil demand, global oil reserves above ground, and the KILIAN Indicator of Global). The research found a set of results, the most important of which is that OPEC plays an active role in the global oil market because it controls one of the main variables that affect global oil prices, which is the global oil supply
Keywords: crude oil; oil prices; global oil supply; global oil demand